Dematerialization of Securities: A Sign of Prosperity of Capital Market - Kansal, Amit (Journal of Commerce and Trade, 2007)
A significance development of the 20th century particularly in its later part is expansion of financial market especially capital market world over which mostly was driven by globalization, technology, innovations and increasing trade volume. India has not been an exception with probably largest number of listed companies with a very large investor population and ever increasing volumes of trades. The increase in trade volumes lead to exponential rise in the back office operations thus limiting the growth potential of the broking members. The inconvenience faced by investors in settlement of trade also limits the opportunity for such investors, especially in participating in auction trading. The physical form of holding and trading in securities also acted a bottleneck for community in capital market operations. Thus the system of security transaction is not as investor-friendly as it ought to be. In this scenario dematerialized trading under depository system is certainly a welcome move.